2016
DOI: 10.1002/jhet.2633
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Novel 1,4‐Phenylene‐bis‐thiazolyl Derivatives and Their Anti‐hypertensive α‐blocking Activity Screening

Abstract: A series of novel 1,4‐phenylene‐bis‐thiazolyl derivatives were synthesized and evaluated for their anti‐hypertensive activities as α‐blocking agents and some of them showed promising activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…In addition, many bis ‐pyrazole and bis ‐1,3,4‐thiadiazole derivatives were reported to exhibit various pharmaceutical, agrochemical, and many other applications including antibacterial, fungicidal, tuberculostatic, antiamoebic, and plant growth regulative properties . In view of these reports and in continuation of our previous works in synthesis of bioactive bis ‐heterocyclic compounds , we report herein the synthesis of bis ‐1,3,4‐thiadiazole derivatives using N′,N″ ‐([1,1′‐biphenyl]‐4,4′‐diyl) bis (2‐oxopropanehydrazonoyl chloride) as common precursor and evaluate these compounds for their antimicrobial activities.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, many bis ‐pyrazole and bis ‐1,3,4‐thiadiazole derivatives were reported to exhibit various pharmaceutical, agrochemical, and many other applications including antibacterial, fungicidal, tuberculostatic, antiamoebic, and plant growth regulative properties . In view of these reports and in continuation of our previous works in synthesis of bioactive bis ‐heterocyclic compounds , we report herein the synthesis of bis ‐1,3,4‐thiadiazole derivatives using N′,N″ ‐([1,1′‐biphenyl]‐4,4′‐diyl) bis (2‐oxopropanehydrazonoyl chloride) as common precursor and evaluate these compounds for their antimicrobial activities.…”
Section: Introductionmentioning
confidence: 89%
“…Continuing our work on bis-heterocycle synthesis [31][32][33][34][35], the starting compound 2,2′-(1,2-diphenylethane-1,2-diylidene)bis(hydrazinecarbothioamide) 2 was obtained via reaction of benzil 1 with thiosemicarbazide in a molar ratio of 1:2 in refluxing EtOH/drops HCl for 3 h using a published procedure [36] (Scheme 1). The second thermal degradation step was sharp and started at 270 • C. The weight losses of chitosan, CLCS and CLCS/MWCNTs composite at 500 • C were 65.46%, 57.95% and 53.29%, respectively (Table 1).…”
Section: Synthesis Of Benzil Bis-thiazolesmentioning
confidence: 99%
“…It has been reported that such compounds possess antitumor properties against a variety of human cancer cell lines [15][16][17]. In continuation to a previous study where we deal with the utility of hydrazonoyl halides for synthesis of various bioactive bridgehead nitrogen polyheterocycles [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], we aim herein to report a new facile synthesis of new imidazo [2,1-b]thiazole-linked thiadiazole conjugates, It is anticipated that the synthesized compounds will have potent pharmacological activities as anticancer agents.…”
Section: Introductionmentioning
confidence: 97%